The socioeconomic impact of the development of Abadaba Lake as a boost to tourism and community development in Imo state Nigeria - Isidiho, Alphonsus O.; Sabran, Mohammad Shatar (Research Institute for Progression of Knowledge, 2015)
The importance and impacts of tourism in development and actualization of the goals of Millennium Development Goals (MDG), particularly concerning poverty alleviation, environmental conservation, and generation of employment opportunities for women and the rural communities is gaining a lot of debate and literature. Furthermore, tourism could be a source of revenue through foreign exchange earnings and tax revenue to the government coupled with the multiplier effects of these revenues and this motivates each country towards developing their tourism potentials. Also of vital benefit is the new dimension in tourism named the ecotourism which has improved greatly the lives of the rural communities in areas where it is practiced. There is overwhelming discussions and reports by individuals, groups, and government and tourism industries of increasingly economic impacts of tourism at national, state, and local levels and not much have been said by the capitalist operators on the sociocultural benefits. The capitalist are more interested in the economic aspect of tourism since their interest is the return on their investment. However, tourism activity also involves economic and sociocultural costs, including the direct costs incurred by tourism businesses, government costs for infrastructure to better serve tourists, as well as congestion and related costs borne by individuals in the community coupled with the pollution of the societal culture through the infusion of foreign cultural and social life style. The importance of the development of Abadaba Lake in Obowo as a tourist location would be of great benefit to the rural community and the state at large. Hence the purpose of this study is to highlight the benefits of tourism worldwide which would also be applicable to Obowo community and Imo state through the development of Abadaba Lake. Secondary data were utilized in the study and the findings shows that in majority of locations, countries and literature, the benefits of tourism outweighs the few negative impacts and with good planning and implementation, monitoring and evaluation, these negative impacts would be controlled. We therefore suggest and encourage the government of Imo State and all the stakeholders to put in place the process of the development of Abadaba Lake as a modern tourist center with state of the art amenities as this would increase the socioeconomic benefits both to the rural communities and the state.